Developing a Shared Understanding of Humanism in Health Care Through Critical Review and Empirical Exploration: Protocol for a Modified e-Delphi Study - Diane Guay; Annie Turcotte; Marie-Josée April; Véronique Foley; Jacinthe Beauchamp; Nicole Marquis; Michèle Héon-Lepage (JMIR Research Protocols, 2026)
Background Humanism is central to the practice of health care professionals but remains poorly defined and inconsistently applied. Amid growing system pressures and dehumanization, this study aims to develop consensus-based conceptual and operational definitions of humanism to support education, evaluation, practice, and policy. Objective This study aims to formulate consensus-based conceptual and operational definitions of humanism in health care, based on the integration of theoretical perspectives with the experiences and expertise of clinician-educators, students, and members of the public. Methods A 2-phase mixed methods design was implemented to ensure methodological rigor and analytical depth. In phase I, a critical review of the literature was conducted and systematically analyzed using content analysis. Concurrently, focus groups were conducted with learners, clinician-educators, and members of the public. The resulting qualitative data were subjected to thematic analysis to capture both the theoretical and experiential dimensions of humanism in health care. Phase 2 will involve a modified e-Delphi technique, in which the generated statements will be submitted to an interdisciplinary and cross-sectoral panel of experts for iterative refinement and validation. This approach is intended to strengthen construct validity and support consensus building. Results This project is funded by the Research Chair in Compassion Science at the Université de Sherbrooke, with additional support from the Office of Social Accountability. The study is currently progressing through phase 1. In step 1 (critical literature review), the initial screening of studies based on titles and abstracts has been completed, and full-text screening is nearing completion. To date, 51 studies have been selected, and data extraction and analysis are underway. In step 2, analysis of data collected from 3 focus groups (N=18) has been completed. The process of converting critical review and focus group findings into Delphi statements is expected to be completed by the end of summer 2026. Phase 2 will consist of a modified e-Delphi process. The launch of this phase, involving the submission of the developed statements to an interdisciplinary and cross-sectoral panel of experts, is scheduled for fall 2026. Conclusions This study is expected to contribute to the development of a conceptually grounded and operationally relevant definition of humanism in health care, informed by both theoretical foundations and lived experiences. This process will support the harmonization of educational practices, the development of assessment tools, and the integration of humanistic values into health policy. International Registered Report Identifier (IRRID) DERR1-10.2196/86055